Quand le syntagme nominal prend ses marques Du prédicat à l'argument - Lauwers, Peter; Paykin, Katia; ILIOAIA, Mihaela; Meulleman, Machteld; Hadermann, Pascale (EPURE, Éditions et presses universitaires de Reims, 2021)
This volume brings together about twenty contributions on the syntax and semantics of predicates and arguments, written by international specialists in the field. The formal architecture of the predicate (verbal and nominal) and the morpho-syntactic means of marking its arguments are addressed, with particular attention to the dative. This book is mainly focused on French, while putting it in perspective with other languages, Romance (Spanish, Romanian), Germanic (Dutch, English) and Slavic (Russian), not to mention the classical languages (Latin, Greek) and Indo-Iranian (Sanskrit).